Analysis and Design of Switched LC Converter With Reduced Voltage Stress for Photovoltaic Applications - Singh A.; Siva V.; Kumar A.; Singh S.K. (My University, 2025)
High step-up voltage conversion is required in renewable energy systems. This paper presents a non-isolated high step-up DC-DC converter based on active switched-inductors (ASL) with switched capacitor cells (SCC). The unique selling proposition of the proposed converter is division of input current which reduces the inductor size. In the proposed topology, the capacitor and diode are arranged in such a way that they interconnect the input to the load side for obtaining high step-up ratio. The main advantages of the converter are high step-up ratio at a low duty cycle with low switch stress and low component count. Operating principles, design equations, and device stress are included in this paper. Moreover, small-signal analysis and its bode plots are presented here. In addition, the loss distribution is critically investigated. Finally, to verify the theoretical study, a laboratory prototype is built and tested at different operating points in continuous conduction mode (CCM). © 1972-2012 IEEE.